Tracing the Trophic Fate of Aquafeed Macronutrients With Carbon Isotope Ratios of Amino Acids - Larsen, Thomas; Wang, Yiming V.; Wan, Alex H. L. (Frontiers in Marine Science, 2022)
Algal ingredients have a number of nutritional and functional attributes that could be exploited to improve growth and health in farmed fish. Typical parameters for testing dietary algal inclusions in aquafeed focus on a suite of immunological parameters in concert with fish growth performance or muscle quality. However, to optimize replacement of fish meal with algal derived ingredients, it is crucial to understand the metabolic fate of algal macronutrients and their nutritional interactions with other ingredients. Here, we review the potential of using an emerging nutritional biomarker in aquaculture, stable carbon isotope (d13C) analysis of single amino acids (AAs). Applications of d13CAA based approaches in fish feeding trials show promise in closing the knowledge gap in terms of understanding how fish assimilate and metabolize algal derived macronutrients. Source diagnostic d13C fingerprints among the essential AAs can trace the protein origins to broad phylogenetic groups such as red macroalgae, brown macroalgae, bacteria, and terrestrial plants. Among the non-essential AAs, d13C patterns can inform about metabolic routing and utilization of dietary lipids and carbohydrates. Despite the potential of d13CAA as a nutritional biomarker, the few applications to date in fish feeding trials warrant further development and implementation of d13CAA based approaches to improve understanding of protein origins and macronutrient metabolic routing.